2003
DOI: 10.1055/s-0040-1715734
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ABR Stimuli for the Early Detection of Ototoxicity: Conventional Clicks Compared with High Frequency Clicks and Single Frequency Tonebursts

Abstract: Effective objective testing methodology is needed for early detection of the effects of ototoxicity on hearing in patients. The requirements for such testing include responses that are: 1) reliable across test sessions; 2) sensitive to ototoxic change (> 8 kHz), and 3) recordable in a time-efficient manner. Auditory brainstem responses (ABR) appear well suited to this task however, conventional clicks stimulate primarily mid-frequencies (1-4 kHz) and high frequency tonebursts require too much time. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The good test-retest reliability of (high-frequency) audiometry is corroborated by studies conducted by Swanepoel et al (2010) and Ishak et al (2011), as well as by several other investigations that employed diverse transducer models (Fausti et al, 1998; Frank, 1990, 2001; Frank & Dreisbach, 1991; Schmuziger et al, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…The good test-retest reliability of (high-frequency) audiometry is corroborated by studies conducted by Swanepoel et al (2010) and Ishak et al (2011), as well as by several other investigations that employed diverse transducer models (Fausti et al, 1998; Frank, 1990, 2001; Frank & Dreisbach, 1991; Schmuziger et al, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…Highfrequency audiometry tests frequencies above 8 kHz (up to 16 or 20 kHz) and allows for the detection of hearing loss before it manifests in the frequencies most important in speech and language (AAA, 2009;ASHA, 1994;Fausti et al, 1992Fausti et al, , 1984Jacobson et al, 1969;Rappaport et al, 1985;Tange et al, 1985). Distortion product otoacoustic emissions are also a convenient and noninvasive method to detect ototoxic change in outer hair cell function (Poling et al, 2012) and are reported to be particularly advantageous in evaluating children and adults unable to respond behaviorally (Dreisbach et al, 2018;Fausti et al, 2003). This is especially important for pediatric patients because it is reported that children identified with hearing loss early and have early intervention strategies minimize the social and intellectual impact of hearing loss (Clemens et al, 2019;Yoshinaga-Itano et al, 1998).…”
Section: Ototoxicity: Protection and Preventionmentioning
confidence: 99%
“…Techniques, such as otoacoustic emissions (OAEs), electrocochleography, and auditory brainstem responses (ABRs), have been used for detecting and monitoring ototoxicity in infants and non-responsive subjects with success. 11 , 12 Among these techniques, ABR is viewed as the most objective and sensitive method capable of exploring the specific brainstem damage pattern formed by ACTs; the exact clinical implication of changes in the responses is, however, still not known. 13 To assure quality ABR testing, methods are required to rule out external or middle ear disease.…”
Section: Introductionmentioning
confidence: 99%